Design of Microcontroller Based Injector Test Kit - Rahmat Hidayat; Dwi Sudarno Putra; Irma Yulia Basri (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
Automotive technology is growing very rapidly. one of the conventional fuel intake systems to the injection system. where is the fuel intake by the ECU based on engine conditions detected by electronic sensors. The injection will work optimally if the injector that is working is not blocked or has problems, the injector determines the smoothness of the injection system. If the injector's performance is less than optimal, the injection system is not optimal and the engine performance is disrupted. To maintain the injector before working optimally, routine cleaning of the injector is carried out, the problem is the scarcity of the injector test equipment encountered in the field because of the high cost of the equipment, therefore the researchers innovated the design of the injector test equipment using EFI fuel system capable of handling problematic injector problems and the scarcity of this tool in the field.